PENGARUH IKLIM ORGANISASI DAN KUALITAS KEHIDUPAN KERJA TERHADAP PRODUKTIVITAS KARYAWAN MELALUI KEPUASAN KERJA DENGAN MODERASI BUDAYA ORGANISASI (Study kasus pada Customer Sales Representative di Gerai Grapari Telkomsel wilayah Jabodetabek – tahun 2020 - Redjeki, Sri; Sihite, Mombang; Supriyadi, Edy (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2021)
This study aims to analyze the influence of the Quality of Work Life and Organizational Climate moderated by Organizational Culture on Employee Productivity through Job Satisfaction as an intervening variable. The type of research in this research is descriptive qualitative research, the population in this study Customer Sales Representative (CSR) Grapari Telkomsel in the region Jabodetabek, samples taken as many as 153 people. Data collection was carried out by distributing questionnaires. The data analysis technique used is SEM analysis with PLS. This research shows that the variables of the quality of work life, organizational climate, have a positive and significant effect on employee productivity through job satisfaction, and the role of organizational culture in moderating organizationalclimate and job satisfaction has a significant effect, while the role of organizational culture in moderating the quality of work life and Job satisfaction directly has no significant effect.Keywords: Organizational Climate, Quality of Work Life, Organizational Culture, Job Satisfaction, Employee Productivity